Peculiarities of Oxidative Polymerization of Diarylaminodichlorobenzoquinones - Andrey V. Orlov (MDPI AG, 2021)
New oxidative polymerization monomers—diarylaminodichlorobenzoquinones were synthesised by alkylating aniline, m-phenylenediamine and methanilic acid with chloranil. Oxidative polymerization of diarylaminodichlorobenzoquinones was studied for the first time in relation to the concentration of the monomer, acid, and oxidant/monomer ratio. It was found that the synthesized monomers are highly active in the polymerization reaction, and the oxidation rate grows with the increase in the acid concentration. Only one arylamine group is involved in the polymerization reaction. The optimal oxidant/monomer ratio is stoichiometric for one arylamine group, despite the bifunctionality of the monomers. It was shown that the type of the substituent in the aniline ring (electron donor or electron acceptor) determines the growth of the polymer chain and the structure of the resulting conjugated polymers. A mechanism for the formation of active polymerization centers for diarylaminodichlorobenzoquinones was proposed. FTIR-, NMR-, X-ray photoelectron spectroscopy, and SEM were used to identify the structure of the synthesized monomers and polymers. The obtained polymers have an amorphous structure and a loose globular morphology. The frequency dependence of the electrical conductivity was studied.